Importance and Role of Upper Gastrointestinal Endoscopy in Diagnosis of Recurrent Abdominal Pain in Children - Irfan Ullah, Muhammad Naeem, Muhammad Bilal, Saima Sajjad, Omer Hassaan Aftab Ahmad, Shirjeel Zaheer (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to determine the effectiveness of upper gastrointestinal endoscopy in diagnosis of recurrent abdominal pain in children. Study Design:Retrospective study. Place and Duration: Department of Gastroenterology, HITEC-IMS Taxila Cantt. 1st July 2021-31st Dec 2021 Methods:There were 78 children of both genders with ages >14 years were presented in this study. After obtaining the authority's informed written permission, we took detailed demographic information, such as age, gender, weight, and symptoms, for all of the recruited patients. All the patients were underwent for upper gastrointestinal endoscopy to diagnose recurrent abdominal pain. Prevalence of dyspepsia and H.pylori infection was also recorded among children. We used SPSS 23.0 to analyze complete data. Results: Among 78 children, 42 (53.8%) were boys and 36 (46.2%) were girls. Majority of the patients 45 (57.7%) were ages between 4-8 years followed by 9-14 years 25 (32.1%) and 8 (10.3%) were in age group 1-3 years. Most common symptom was anemia, followed by vomiting, haematemesis, melena and weight loss. Frequency of dyspepsia was found in 22 (28.2%) and helicobacter pylori found in 29 (37.2%) children. Most common diagnosis of endoscopy was gastritis found in 33 (42.3%) case, gastric erosions in 14 (17.9%) cases, hiatus hernia in 8 (10.3%) cases and remaining were gastric ulcer, gastric polyp and duodenitis. Hypoxemia, apnea and aspirationwere the most common complications found in our study. Conclusion: In this study, we found that upper gastrointestinal endoscopy remains an essential tool in the evaluation of RAP in children because it allows for accurate diagnosis of GI causes of RAP, despite reported complications such as hypoxemia, apnea, aspiration and choking, cardiac arrhythmias, bacteremia, perforation, and bleeding.